1999
DOI: 10.1063/1.1301408
|View full text |Cite
|
Sign up to set email alerts
|

L-R asymmetries and signals for new bosons

Abstract: Several left-right parity violating asymmetries in lepton-lepton scattering in fixed target and collider experiments are considered as signals for doubly charged vector bosons (bileptons).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…7,14-16 Ab initio modeling calculations have shown that the electrophilic attack for branching should be the most prevalent of the two mechanisms, since the Diels-Alder reaction is not energetically favorable and considerable steric hindrance would also be a negative factor toward this reaction. 41 Quantification of crosslinking in regards to branching and Diels-Alder for the polymer chains is theoretically possible from the NMR spectra of the reaction over time. 6 Identification of peaks that correspond to a branching product proved difficult since all of the peaks that would be indicative of branching are also found in linear polymeric chains.…”
Section: Spectral Analysis Of Pfa and Poly(2-fe) Oligomersmentioning
confidence: 99%
“…7,14-16 Ab initio modeling calculations have shown that the electrophilic attack for branching should be the most prevalent of the two mechanisms, since the Diels-Alder reaction is not energetically favorable and considerable steric hindrance would also be a negative factor toward this reaction. 41 Quantification of crosslinking in regards to branching and Diels-Alder for the polymer chains is theoretically possible from the NMR spectra of the reaction over time. 6 Identification of peaks that correspond to a branching product proved difficult since all of the peaks that would be indicative of branching are also found in linear polymeric chains.…”
Section: Spectral Analysis Of Pfa and Poly(2-fe) Oligomersmentioning
confidence: 99%
“…After integrating the super-Lagrangian given in Eqs. (14,15,16) and Eq. (18), we obtain the Lagrangian given in Appendix A.…”
Section: The Supersymmetric Termsmentioning
confidence: 99%
“…There exists another interesting possibility (ϑ = 1/ √ 3), where a left-handed anti-neutrino to each usual SU(2) L doublet is added to form an SU(3) triplet (ν, l, ν c ) L [4], and this model is called the 3-3-1 model with RH neutrinos. The 3-3-1 models have been studied extensively over the last decade, see for example [14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The supersymmetric 3-3-1 model is employed by J.C. Montero, V. Pleitez, M.C. Rodrigues to calculate the neutralinos and charginos masses, and to emphasize the difference in the generation of lepton mass production mechanism with the usual 3-3-1 and the minimal SUSY model [10].…”
Section: Oral Communications and Postersmentioning
confidence: 99%